Islamic Philanthropy and Women's Empowerment at the Zakat Management Institution Bandar Lampung - Suslina, Suslina (Al Huwiyah: Journal of Woman and Children Studies, 2023)
In the women's empowerment sector in utilizing the potential of zakat in society, it is very promising to improve the fate and status of women in a better direction. This hope can be realized when women unite to contribute in exploring the potential of zakat by maximizing the receipt of zakat through awareness of the obligatory zakat. Especially those with middle to upper income. So through zakat women who live on the poverty line can use it by increasing working capital to improve their quality of life. The aim of this research is; 1) To find out the function of the Zakat Management Institution in the implementation of zakat which is defined as women's empowerment. 2) Looking for interaction between women's empowerment and the implementation of zakat, as well as contributing ideas towards empowering women as well as empowering the implementation of zakat in the City of Bandar Lampung. The methodology of this research is field research (fild research) with a qualitative approach. The conclusion of this research is; 1) Structurally, the management and distribution of zakat in the city of Bandar Lampung is undeniable that women intervene. This is part of the form of public awareness and concern, that women are also able to play a role in the management and empowerment of zakat. 2) The empowerment program carried out by the amil zakat institution in Bandar Lampung City has been carried out, although it has not been maximized. Empowerment that touches on productive business development also has not received special attention, so that the role of women in this context does not directly lead to empowerment in the sense of a special program, in carrying out its movement, the Amil Zakat Institution in Bandar Lampung City holds the spirit of Islamic goals in zakat matters adhering to Law no. 23 of 2011 concerning Zakat Management.